PENGARUH BLACKBERRY MESSENGER TERHADAP INTERAKSI SOSIAL SISWA SEKOLAH MENENGAH ATAS NEGERI 6 PEKANBARU - ANNISA, NURUL; ", RUMYENI (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The development of communication technology has resulted a revolution of communications. The communication technology has also made it easy for people to communicate with others. One of the most popular of communications today is BlackBerry Messenger. BlackBerry Messenger is an instant messaging program which is available for BlackBerry smartphone users. BlackBerry Messenger app is one of the facilities that makes BlackBerry becomes attractive enough for people to use. The application attracted the attention of students, so it takes students’ time and interactions that should have been done in person directly. This study aims to determine how much BlackBerry Messenger influence students’ social interaction in SMAN 6 Pekanbaru.The method that was used in this study is a survey explanatory. To collect the data, the authors used questionnaires and documentation. To determine the effect of BlackBerry Messenger on students’ social interaction in SMAN 6 Pekanbaru, the authors used a simple linear regression analysis. Variable X in this study is the BlackBerry Messenger, while variable Y is. The number of samples in this study was 87 students, sample collection technique is random sampling technique. Processing test questionnaires were performed using the Statistics Product and Service Solutions (SPSS) version 16.0.Results of this study demonstrate the effect of influence of BlackBerry Messenger on students’ social interaction in SMAN 6 Pekanbaru is 11.1%. It is based on analysis of the data using a simple linear regression is Y = 12.800 + 0.258 X with t 3262 greater than the t table 1.988 and the significance level is 0.002 less than α = 0.05. Therefore H0 is rejected and H1 is accepted because there is influence or effect of BlackBerry Messenger on students’ social interaction in SMAN 6 PekanbaruKeywords: BlackBerry Messenger, Social Interaction, Student.